Polymorphic Diversity of Actin-Like Protein from cDNA Isolated from Korean Native Chicken - Sun, S.S.; Myung, K.H.; Kuk, K.; Kim, N.O. (International Journal of Poultry Science, 2006)
We report the isolation and characterization of a chicken cDNA which putatively encodes a chicken actin-like protein (cALP). A clone, KNC-NDS-7 (Genbank, access No, AY466164.1) will be a other form of actin-like protein with these low about 10% homology. DNA sequence (34 - 748 nt) of KNC-NDS-7 was translated into amino acids (237aa) which was compared with actin-like protein of 99% homology with chicken. We found that three important sites have been deleted or substituted. Thereafter, the amino acid profile has been changed. The deleted site (729-731 nt) was not translated to glutamate (E), and the substituted site (711-714 nt) was expressed to leucine (L) instead of proline (P) in the all other species. The third position (465-459 nt) was changed to lysine and threonine (KT) instead of glutamine and lysine (QK). These changes will have important affect to actin structure in KNC. In these results, KNC-NDS-7 is may another form of acin-like protein.